(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The economic and social development of any country is highly dependent on health. National initiative to curb the dangers of student’s ill health and social wellbeing in Nigeria is still lacking. The study is aimed to investigate the oxidative stress and antioxidant status of newly admitted undergraduate students who fell sick within 12 months period of stay in Nnamdi Azikiwe University, Awka, Nigeria. Materials and Methods: This is a longitudinal prospective study involving 530 (male=239, female=291) apparently healthy newly admitted 100 level students (control) and 354 (male-169, female=185) students who fell sick within 12 months period of stay in school (test). The test group was group into A (malaria, n=112), B (typhoid, n-61), C (malaria/typhoid, n-103), D (pneumonia, n=31) and E (peptic ulcer disease, n=47). Serum concentrations of malondealdehyde (MDA), nitric oxide (NO), total antioxidant capacity (TAC), catalase (CAT) andglutathione (GSH) were determined. Results: The results showed significantly increased levels of MDA, NO with decreased TAC, GSH and CAT in sick undergraduate students especially in malaria, typhoid, malaria/typhoid and peptic ulcer group compared with apparently healthy participants (P<.05 respectively). Same pattern was observed in male than in female sick participants (P<.05 respectively). Conclusion: The alteration in pro-oxidant markers is accompanied with imbalance in the antioxidant defense status resulting in oxidative stress. Males were more susceptible to oxidative insult than females. This shows that oxidative stress may have contributed to the pathogenesis and severity of different diseases observed which may cause irreversible cell damage if not managed. A national intervention for student’s health and social wellbeing is strongly advocated.